Development of Multi- Agent Simulation Model to Uncertain Civilian Return Trips during a Hypothetical Earthquake - Seiichi Kagaya; Masato Sasaki (European Regional Science Association (ERSA), 2013)
Through the experiences of the Great 1994 Hanshin-Awaji earthquake and The Great 2011 (Higashi-Nihon) East Japan Earthquake, it has been important for Japanese local Government to build a comprehensive evacuation program on a large earthquake occurrence in near future. According to the experts' forecast,a huge earthquake will occur around the coast areas of Pacific Ocean in Japan in near future. Therefore, it is indispensable to give appropriate information on human behavior for the evacuation time.It is also necessary to urge the residents to select exact behavior. Thus, a new methodology based on behavior-oriented agent system should be developed to understand group activities. In this study, the production rules of the attributive groups were constructed in terms of the questionnaire survey for civilian return-trips from the working offices or the shopping places during earthquake disaster. Next, using the set of production rules composed of the questionnaire data, a multi-agent system model for return trips in a hypothetical large-scaled earthquake was built by a MAS method. The simulation was tried using specific data on the Person Trip Survey. It comes to the conclusion that the human behaviors during the earthquake impact were constructed by multi-agent system model and the possibility of the return-home was found in view of the conditions of the roads and the human attributes.
Keywords: 330; Multi-agent system; Simulation model; Binomial logit model; Earthquake disaster